The Influence of Artificial Intelligence on Revenue Performance: Evidence from Platform-Based Illustrators - Fitria Ayu Lestari Niu; Shadrina Hadis; Radlyah Hasan Jan; Jamaludin Hasan (AIBPM Publisher, 2026)
Artificial Intelligence (AI) has reshaped the competitive landscape of the platform-based creative economy and has implications for the sustainability of digital business actors' income. This study empirically examined the influence of AI development on the income performance of illustrators on platform X (Twitter) from an accounting and financial perspective. This study used an explanatory quantitative approach, involving 385 illustrators from the Artist's Base community, selected using simple random sampling. Data analysis was performed using simple linear regression to identify the relationship between AI-based competitive pressures and illustrator income levels. The results showed that AI had a significant effect on illustrators' income (b = 0.330, p 0.05; R² = 7.4%). These findings indicate that AI serves as a financial risk factor, increasing price pressures, enhancing market transparency, and increasing exposure to revenue volatility. However, its contribution to income variation is relatively limited, so other strategic factors, such as the differentiation of work, digital reputation, and adaptability to the dynamics of the digital creative market, continue to influence illustrators' financial sustainability. This study contributes to the accounting literature by positioning AI as a measurable financial determinant rather than a pure technological innovation.